2019
DOI: 10.1093/mnras/stz3624
|View full text |Cite
|
Sign up to set email alerts
|

Colliding winds in and around the stellar group IRS 13E at the galactic centre

Abstract: IRS 13E is an enigmatic compact group of massive stars located in projection only 3. 6 away from Sgr A*. This group has been suggested to be bounded by an intermediate-mass black hole (IMBH). We present a multi-wavelength study of the group and its interplay with the environment. Based on Chandra observations, we find the X-ray spectrum of IRS 13E can be well characterized by an optically thin thermal plasma. The emission peaks between two strongly mass-losing Wolf-Rayet stars of the group. These properties ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Based on this scenario, we compare the results of the numerical simulation with the observed eccentricity distribution of the CWSs to constrain the IMC's orbital semi-major axis to be in the range of 0.3 − 0.4 pc which is somewhat larger than IRS 13E's projected separation from Sgr A as suggested by the X-ray morphology of its surrounding region (Wang et al 2020). We also find that for a co-orbiting IMC, the effectiveness of this process requires the depletion timescale (τ dep ) to be comparable to or larger than a fraction of the liberation timescale.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this scenario, we compare the results of the numerical simulation with the observed eccentricity distribution of the CWSs to constrain the IMC's orbital semi-major axis to be in the range of 0.3 − 0.4 pc which is somewhat larger than IRS 13E's projected separation from Sgr A as suggested by the X-ray morphology of its surrounding region (Wang et al 2020). We also find that for a co-orbiting IMC, the effectiveness of this process requires the depletion timescale (τ dep ) to be comparable to or larger than a fraction of the liberation timescale.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recent ALMA observations also unveiled ionized gas which appears flowing along eccentric Keplerian streams around a point-mass potential at the location of IRS 13E (Tsuboi et al 2017). However, this interpretation would break down if the gas properties of IRS 13E is due to a colliding winds (Wang et al 2020;Zhu et al 2020). Although the suggestion that it may be an intermediatemass black hole (IMBH) remains a controversial issue (Maillard et al 2004;Hansen & Milosavljević 2003;Kim et al 2004), its total inferred mass (∼ 10 4 M ) would be reasonable if the young stars in the IRS 13E complex are gravitationally bound (Schödel et al 2005;Tsuboi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The relation of E60 to IRS13E is unclear, but its proper motion along R.A. has a value of -210 km s −1 , quite comparable to the mean value of E1, E2 and E4. Wang et al (2020) suggested that E60 is an interacting binary emitting X-rays and may alone be responsible for the flux associated with what we refer to as the "tail". The X-ray intensity profile examined in Figure 3 instead suggests a continuous distribution rather than a sum of two overlapping point sources.…”
Section: Discussionmentioning
confidence: 99%
“…During the final preparation stage of our manuscript,Wang et al (2020) published a study of IRS13E, which also identifies its extended X-ray morphology based on a similar set of Chandra data. Our interpretation for this morphology is different from theirs, as will be explained in later Sections.3 http://cxc.harvard.edu/ciao…”
mentioning
confidence: 99%
“…Other observations that can be explained by the impact of the jet with the mini-cavity is an X-ray source with a luminosity of 2×10 33 erg s −1 coincides with the cluster of stars, IRS 13E, (Wang et al 2020;Zhu et al 2020) embedded within the western edge of the minicavity. Recent analysis of X-ray data concludes that colliding winds of masslosing stars in the cluster are responsible for production of X-rays (Wang et al 2020;Zhu et al 2020). Alternatively, we note that X-ray emission from the minicavity can also be explained by the violent collision with the jet shocking the gas to high temperatures.…”
Section: Collimated Outflow and Interaction Sitesmentioning
confidence: 95%